Dynamic GATA6 Expression in Primitive Endoderm Formation and Maturation in Early Mouse Embryogenesis - Cai, Kathy Q. (2008)
The derivation of the primitive endoderm layer from the pluripotent cells of the inner cell mass is one of the earliest differentiation and morphogenic events in embryonic development. GATA4 and GATA6 are the key transcription factors in the formation of extraembryonic endoderms, but their specific contribution to the derivation of each endoderm lineage needs clarification. We further analyzed the dynamic expression and mutant phenotypes of GATA6 in early mouse embryos. GATA6 and GATA4 are both expressed in primitive endoderm cells initially. At embryonic day (E) 5.0, parietal endoderm cells continue to express both GATA4 and GATA6; however, visceral endoderm cells express GATA4 but exhibit a reduced expression of GATA6. By and after E5.5, visceral endoderm cells no longer express GATA6. We also found that GATA6 null embryos did not form a morphologically recognizable primitive endoderm layer, and subsequently failed to form visceral and parietal endoderms. Thus, the current study establishes that GATA6 is essential for the formation of primitive endoderm, at a much earlier stage then previously recognized, and expression of GATA6 discriminates parietal endoderm from visceral endoderm lineages.